Enterobacterias de la paloma de castilla Columba livia en la ciudad de Lima, Perú - Carlos, Nancy; Tafur, Eduardo; Solano, Elizabeth; Alcazar, Paloma (Salud y Tecnología Veterinaria, 2017)
The rock dove Columba livia is an exotic and feral bird that has been described as carrying various agents potentially pathogenic to man and other birds, including bacteria such as Salmonella spp. and E. coli, however, there are few studies regarding infectious disease agents carried by the species in our country. The objective of the study was to determine the enterobacterias present in this free-living bird resident in the City of Lima. During the months of June and July of 2014, 27 adult individuals of C. livia were captured in two zoos located in the districts of Chorrillos and San Juan de Miraflores. A cloacal swab was made to each bird and transported in the Cary Blair transport medium at 4 °C to a private laboratory. In the laboratory, samples were plated on McConkey agar and SS agar, and then proceeded to the identification using biochemical tests (TSI, LIA, Indol, SIM, Citrate, Methyl Red and Voges Proskauer). A total of 35 bacterial colonies were isolated 85.19 % (23/27) from the samples: 62.96 % (17/27) Escherichia coli, 11.11 % (3/27) Enterobacter aerogenes, 11.11 % (3/27) Klebsiella sp., 11.11 % (3/27) Proteus vulgaris, 7.41 % (2/27) Salmonella pullorum, 14.29 % (14/27) Shiguella sp., 11.11 % (3 / 27) Staphylococcus aureus and 3.70 % (1/27) Staphylococcus sp. Here, we report a high frequency of enterobacteria of interest in public health, evidencing the importance of considering rock dove as a reservoir for zoonotic bacteria.